Grain-size distribution of sediment in the vicinity of Setiu Lagoon-estuary system - Yaacob, Rosnan; Husain, Mohd Lokman; Mohd Shazili, Noor Azhar (Universiti Putra Malaysia Press, 1995)
The sediments in the Setiu Lagoon-estuary system on the east coast of Malaysia consist mostly of coarse to very fine panicles. The major portions of the sediment are negatively skewed. The estuary area is under the influence of transportative and erosive forces. The lack of silt and clay in the estuary is attributable to less depositional factor under the influence of stronger current than in the lagoon area. The beach sediment ranges from coarse to fine sand. Generally, the mean grain-size decreases towards the north-west sector. The skewness value of the beach sand area is mostly negative, indicating that the study area is under the influence of rather strong wave and current action.